Trafülkantun cantos cruzados entre Garrido y Curilem - Jordán, Laura (Ariadna Ediciones, 2022)
Trafülkantun is an eclectic study of the relationship between two exceptional figures around the middle of the 20th century: Pablo Garrido Vargas (1905-1982), jazz pioneer, historian of the cueca and leader for the labor rights of musicians and artists, along with Juan Curilem Millanguir (1912-1985), Mapuche intellectual descendant of the Longko family, state professor, musician and choral director, president of the political organization Unión Araucana. Their mutual work shows an unexplored collaborative, intercultural and anti-colonial power, very early for the time. The structure of the book consists of a critical study, the commented edition of five unpublished texts by both authors and seven ülkantun/ songs compiled by Curilem plus annexes.